Influence of Age on Kraft Pulping of Akashmoni (Acacia auriculiformis) Wood Species of Chattogram Hill Tract - Misbahuddin, M.; Khatun, Nazma; Khatun, Nazma; Islam, M. Nesarul; Biswas, D.; Roy, U.; Islam, M. Nesarul; Roy, U.; Biswas, D. (Indian Forester, 2022)
This work evaluated the effect of cooking time, temperature and active alkali on different age group of akashmoni wood species. Pulps have been prepared from akashmoni at ages of 4, 6, 8, 10 and 12 years with kaft process. Cooks were made with active alkali and maintaining sulfidity 25% at 170Â°C. Pulp yield varied from 61.05 to 43.73% of various ages for akasmoni. Kappa number was found is bleachable grade for 6 and 8 years old akasmoni wood and others ages did not give bleachable grade pulp. The physical strength properties of akasmoni like tear, tensile and burst strength were determined. Paper properties of akashmoni kraft pulp compared favorably with those of other hardwood pulp are widely used in the world. Fair grade pulp is produced from eight year akashmoni wood.